TINGKAT PENGETAHUAN IBU TENTANG GIZI SEIMBANG DALAM PEMBERIAN ASI - Endang Buda Setyowati (Akademi Kebidanan Griya Husada Surabaya, 2018)
The number of breastfeeding mothers in DKT Gubeng Hospital Corner from 2015 to 2016 decreased by 27.4% to 24.69%. In addition, a preliminary survey of mother's knowledge about balanced nutrition in breastfeeding, from 10 mothers, found 30% were less knowledgeable, 40% were knowledgeable enough, 30% were knowledgeable. While mothers who give ASI 30% and do not give 70% ASI. Based on this problem, it is deemed necessary to conduct research that aims to describe the mother's knowledge about balanced nutrition in breastfeeding. Method: This study uses descriptive methods. The population in this study were all mothers who brought infants aged 1 to 9 months (mothers who took their children with immunization in the DKT Gubeng Pojok Hospital) were 64 people. Sampling is done by Non Probability Sampling which is using Accidental Sampling of 64 people using a questionnaire then processed using frequency tables and cross tabulation. Results: The results of the research that have been conducted showed that the majority of mothers who gave good knowledge of breastfeeding (66.67%) and mothers who did not provide ASI were mostly knowledgeable (66.67%) Discussion: The majority of mothers who gave breastfeeding had good knowledge about balanced nutrition and mothers those who do not give ASI the majority are knowledgeable about balanced nutrition. So as a health worker can provide counseling, especially to mothers about balanced nutrition breastfeeding mothers and the importance of giving ASI, so that the hope of all mothers can provide breastfeeding can be realized. Support from the husband and family is very important especially in supporting the mother to consume nutritious balanced foods and provide breast milk to her baby.